Limitations to plant diversity and productivity in restored tallgrass prairie - McCain, Kathryn Nicole Schmitt (Kansas State University, 2008)
Approximately 96% of native tallgrass prairie in North America has been lost, which accentuates the need for effective methods to restore the structure and function of these degraded ecosystems. Many prairie restorations aim to restore grass and forb species in proportions reflecting plant species diversity in native prairie. A target grass-forb species mixture is typically chosen at the onset of restoration, but often, grasses become excessively dominant and forbs are underrepresented as the community develops. Several studies have examined the potential for increasing forb cover and diversity in newly restored grasslands, but few studies have assessed factors limiting forb cover and diversity in well-established grass-dominated prairie restorations. The primary objective of this research was to assess the potential for enhancing plant species diversity and productivity in an established grass-dominated prairie restoration by selective removals of dominant grass species, and by manipulating resources (soil nutrients, light availability) or mycorrhizal interactions. A 7-year old grass-dominated restoration was used to evaluate plant and soil responses to manipulations in three separate studies. The first study examined the potential suppressive effects of dominant grasses on plant diversity by reducing the cover and biomass of two dominant grass species, Andropogon gerardii and Panicum virgatum. After 3 years, the removal of A. gerardii increased species richness and diversity, which was correlated with increased light availability, but not changes in soil resources. The second study examined the responses of restored grassland communities to long-term manipulation of soil resources (nutrient availability or soil depth), and to aboveground biomass removal via mowing. The long-term manipulation of soil resources did not alter plant species diversity, but nitrogen and light availability were important factors regulating plant productivity. The third study assessed the effects of manipulating arbuscular mycorrhizal (AM) fungi, through the use of either commercial inoculum or fungicide, on plant communities in restored prairie. Mycorrhizal suppression reduced grass productivity, suggesting that fungicide may be useful for enhancing diversity of restored prairies that are dominated by obligate mycotrophic grasses. In total, these studies suggest that competition between dominant grasses and subordinate forbs limits plant diversity in restored tallgrass prairie.
Keywords: tallgrass prairie; restoration; plant diversity; Biology, Ecology (0329)